1999
DOI: 10.1192/pb.23.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Malaise in psychiatric recruitment and its remedy

Abstract: Aims and methodSurveys of career intention among medical students, Membership Examination results and manpower figures are used to examine trends in recruitment to psychiatry over the last 10 years.ResultsProblems of recruitment to psychiatry have increased. Consultant expansion contrasts with a fall in the number of medical students. The increase in the number of career senior house officers and specialist registrars is insufficient to fill existing consultant vacancies notwithstanding new and replacement pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…This is consistent with previous work that suggested that the divorce of psychiatry from mainstream medicine had led to its relative unpopularity (Thompson & Sims, 1999). Galeazzi et al (2003) found that the perception of psychiatric care as evidence based and recognition of research opportunities in mental health were important factors that led to the choice of psychiatry as a career.…”
Section: Reasons For Choosing Psychiatrysupporting
confidence: 80%
“…This is consistent with previous work that suggested that the divorce of psychiatry from mainstream medicine had led to its relative unpopularity (Thompson & Sims, 1999). Galeazzi et al (2003) found that the perception of psychiatric care as evidence based and recognition of research opportunities in mental health were important factors that led to the choice of psychiatry as a career.…”
Section: Reasons For Choosing Psychiatrysupporting
confidence: 80%
“…To this end it is essential that psychiatrists involved in teaching are motivated and that clinical teaching is presented in an interesting and engaging manner with emphasis on the diverse treatment options available and the fact that the majority of psychiatric cases have a good outcome. Clearly at present this is not being achieved, as many junior doctors do not feel confident managing psychiatric patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the relationship of psychiatry with other specialties, and in particular general practice, is interesting as it also has relevance to the recruitment of psychiatric residents. Thompson [38], examining medical career choices in the UK, described a decline in the popularity of general practice and suggests that this is likely to decrease the number of entrants into psychiatry. However, in our study, interest in psychiatry did not correlate with a career interest in general practice or its perception.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students have negative attitudes towards mental illness 4 . Mentally ill patients are affected by the negative prejudices and cultural stereotypes of the public 5 . Surprisingly this problem is noted even among medical students who, despite receiving education on psychiatry, still harbor an unhealthy attitude about mentally ill patients and psychiatric practices 6,7 .…”
Section: Introduction ᴪmentioning
confidence: 99%